1995
DOI: 10.1007/bf01833870
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbiological flora and sexually transmitted diseases in women with recurrent or current vulvovaginal candidiasis

Abstract: A history of recurrent vulvovaginal candidiasis (RVVC) was reported by 102 women, while current vulvovaginal candidiasis (VVC) was diagnosed in 83 of the same 996 women. They had all attended two family planning and one youth clinic, respectively. Two women, without RVVC or VVC, matched for age for each case of RVVC, were selected as a comparison group (COMP). Recurrent, but not current VVC, was associated with a history of sexually transmitted disease. Those with current, but not with recurrent, VVC had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…Control and VVC groups did not differ in Lactobacillus counts (P ϭ 0.543) (Table 1), in agreement with Sobel and Chaim (14), but contrary to Zdolsek et al (21), who found more lactobacilli in VVC patients. Healthy and VVC groups exhibited higher counts than the BV group (P Ͻ 0.001).…”
supporting
confidence: 88%
“…Control and VVC groups did not differ in Lactobacillus counts (P ϭ 0.543) (Table 1), in agreement with Sobel and Chaim (14), but contrary to Zdolsek et al (21), who found more lactobacilli in VVC patients. Healthy and VVC groups exhibited higher counts than the BV group (P Ͻ 0.001).…”
supporting
confidence: 88%
“…The factors determining whether women with an infrequent history of VVC will acquire a symptomatic infection are not clear; there was no demonstrable effect of inoculum concentration, vehicle, stage of the menstrual cycle, or bacterial flora. There are conflicting reports of an inverse relationship between BV and VVC (20,25,35). However, in this study BV was equally common in those with and without a history of VVC and did not appear to influence the outcome.…”
Section: Vol 72 2004 Live C Albicans Vaginal Challenge In Women 2943contrasting
confidence: 51%
“…6 In contrast, Bacterial vaginosis is characterized by a lack of normally protective lactobacilli and an overgrowth of mainly anaerobic bacteria. 7,8 Because lactobacilli are part of the main defense mechanisms of the vagina, changes in the proportions of these Lactobacillus species are risk factors for developing vaginal infections.…”
Section: Discussionmentioning
confidence: 99%